Constrained catecholamines gain β2AR selectivity through allosteric effects on pocket dynamics - Xu, Xinyu; Shonberg, Jeremy; Kaindl, Jonas; Clark, Mary J.; Stößel, Anne; Maul, Luis; Mayer, Daniel; Hübner, Harald; Hirata, Kunio; Venkatakrishnan, A. J.; Dror, Ron O.; Kobilka, Brian K.; et al. (Nature Communications, 2023)
G protein-coupled receptors (GPCRs) within the same subfamily often share high homology in their orthosteric pocket and therefore pose challenges to drug development. The amino acids that form the orthosteric binding pocket for epinephrine and norepinephrine in the β1 and β2 adrenergic receptors (β1AR and β2AR) are identical. Here, to examine the effect of conformational restriction on ligand binding kinetics, we synthesized a constrained form of epinephrine. Surprisingly, the constrained epinephrine exhibits over 100-fold selectivity for the β2AR over the β1AR. We provide evidence that the selectivity may be due to reduced ligand flexibility that enhances the association rate for the β2AR, as well as a less stable binding pocket for constrained epinephrine in the β1AR. The differences in the amino acid sequence of the extracellular vestibule of the β1AR allosterically alter the shape and stability of the binding pocket, resulting in a marked difference in affinity compared to the β2AR. These studies suggest that for receptors containing identical binding pocket residues, the binding selectivity may be influenced in an allosteric manner by surrounding residues, like those of the extracellular loops (ECLs) that form the vestibule. Exploiting these allosteric influences may facilitate the development of more subtype-selective ligands for GPCRs.
CRIS-Team Scopus Importer:2023-04-28